A Comparison of Abundance and Diversity of Epiphytic Microalgal Assemblages on the Leaves of the Seagrasses Posidonia oceanica (L.) and Cymodocea nodosa (Ucria) Asch in Eastern Tunisia. (2nd June 2014) - Mabrouk, Lotfi; Ben Brahim, Mounir; Hamza, Asma; Mahfoudhi, Mabrouka; Bradai, Med Najmeddine
Abstract : We studied spatial patterns in assemblages of epiphytic microalgae on the leaves of two seagrass species with different morphologies and longevity, Cymodocea nodosa and Posidonia oceanica, which cooccur in Chebba in Eastern Tunisia. Epiphyte assemblages were described for each species in summer. Epiphyte microalgal assemblages were more abundant on the leaves of C. nodosa but more diversified on the leaves of P. oceanica . We suggest that the differences in species composition and abundance between those seagrass species may reflect an interaction of timescales of seagrass longevity with timescales of algal reproductive biology. Short-lived C. nodosa was dominated by fast growing species such as the cyanobacteria species Oscillatoria sp., while P. oceanica leaves were colonized by more mature and diversified species such as Prorocentrales. Local environmental conditions (hydrodynamics, light penetration), host characteristics (meadow type, shapes forms of leaves, life span, and growth rate), and grazing effect seem also to be responsible for these dissimilarities in epiphytic microalgae communities.